DEVELOPMENT STRATEGY OF AGROTOURISM IN CIGUGUR AREA, KUNINGAN - DESTRIANA (NIM : 95714301), NEFALIANTI
Kuningan is one of West Java tourism development zones are included into the development WP Ciayumajakuning. Accordingly, in an early draft Long Term Development Plan (RPJP) of Kuningan (2008-2027), it has a vision to create a districts that upholds the concept agropolitan and excellent tourism in West Java in 2027. Cigugur is one area in Kuningan included in the priority tourism and agropolitan development, because it has many agricultural potential and attractions. The potential contained in Cigugur area can be developed into a tourist destination mainly related to the development of agrotourism. Agricultural potential available in the area, including: dairy farm, vegetable fields, fruit gardens and other rice fields. But now, the tourist destinations associated with agricultural potential emerging only dairy farm who has become one of the attractions are interested visitors when they comes to Cigugur area, while other agricultural potential has not been planned into a tourist attractions. In addition, this area has many other interesting tourist attraction, especially cultural tourism / history are quite closely related to the concept of local farming culture. Therefore, in order to merge agricultural potential and cultural tourism in Cigugur, proposed the development of agrotourism concept combined with cultural tourism as a supporter development strategy of agrotourism that has a different characteristic from other places. This study aims to formulate a recommendation development strategy of agrotourism in Cigugur area as a tangible implementation of tourism development policy in Kuningan. Methodology of this study uses qualitative and quantitative approaches. Primary data were obtained from observations, interviews with relevant stakeholders, the deployment of as many as 100 questionnaires were distributed to tourist who come to each attractions is already available in Cigugur, and giving questionnaire to assess the fulfillment of 12 stakeholder selected. While secondary data obtained from government offices, related books and journals, policy, information from the manager of attractions in there, and internet. For the processing of data associated with the identification of potential tourism in Cigugur, use some supporting software such as Microsoft Excel and SPSS 18 for processing questionnaire data and descriptive analysis based on the observation. For the analysis stage, this research used Multi Criteria Analysis (MCA) as analysis used to formulate the criteria, indicators and benchmarks, whose judgment can be taken into consideration in the formulation of regional development strategy recommendations. The results of this study, in the form of regional development strategy recommendations agrotourism based on culture in Cigugur is medium term, it ranging between 1 (one) to 5 (five) years. The recommendations obtained from the MCA based on priorities of development and has been adapted to the direction RIPPDA and RPJP of Kuningan (2008-2027), so development priorities of the strategic plan regional development in a row which includes aspects of the development of tourist destinations, include the development of: (1) attractions; (2) tourism and public facilities; (3) readiness and community involvement; (4) potential market; (5) accessibility; (6) position of the region; and (7) tourist activities. Recommended strategy is expected to optimize the potential of tourism provided by considering aspects of sustainability in Cigugur.